Pilot training and English as a lingua franca: some implications for the design of Aviation English for ab initio flight training courses - Bieswanger, Markus; Prado, Malila Carvalho de Almeida; Roberts, Jennifer (The ESPecialist, 2020)
This paper revisits discussions on needs assessment of language courses for non-native English speakers (NNES) prior to ab initio flight training, or initial flight training, in English-speaking environments. The growing need for pilots in areas of the world where English is traditionally not the native language of the population and the fact that many of them attend flight school in English-speaking countries have increased the demand for such courses. Important questions are what communicative competencies the future flight students need and how current research on English as a lingua Franca (ELF) can inform the design of English for flight training courses. The paper presents the results of a study based on semi-structured interviews with six non-native speaking professional pilots who received ab initio training in English-speaking countries. The analysis suggests that NNES ab initio flight students need to be equipped with the right mix of communicative strategies often summarized as ELF awareness and a sufficient amount of English language proficiency.